An efficient production of high-pure xylooligosaccharides from corncob with affinity adsorption-enzymatic reaction integrated approach. (October 2017) - Chang, Siyuan; Chu, Jianlin; Guo, Yalan; Li, Huo; Wu, Bin; He, Bingfang
Graphical abstract: Highlights: Fusion enzyme exhibit a high activity and expression level than native xylanase. Fusion enzyme affinity adsorbed on the corncob substrate. The yield of XOS was 6.91 mg/mL through fusion enzyme hydrolysis. XOS with high purity of 91.7% was obtained by centrifugation. Abstract: Xylooligosaccharides (XOS) are high value-added ingredients for functional foods and they have potential use as prebiotics. In order to reduce the production cost of XOS, we constructed a fusion enzyme consisting of expansin and endo -xylanase from B. subtilis Lucky9 to produce high-pure XOS with affinity adsorption-enzymatic reaction integrated approach. By optimization of inserting linker, the specific xylanase activity of fusion enzyme with R2 linker was increased 1.28-fold than that of native xylanase. Electrophoretic pure fusion enzyme was separated from crude enzyme extracts by affinity adsorption on corncob substrate, with 90.3% recovery in optimized conditions. Then, the fusion enzyme-corncob mixture was directly hydrolyzed. The yield of XOS reached 6.91 mg/mL. The production of XOS with high purity of 91.7% was obtained by one step of centrifugation. This affinity adsorption-enzymatic reaction integrated XOS production approach provides a green route to alternative XOS traditional enzymatic production.